2002
DOI: 10.1159/000069044
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nNOS and iNOS following Hypoxia-Ischaemia Improves Long-Term Outcome but Does Not Influence the Inflammatory Response in the Neonatal Rat Brain

Abstract: In this study, we tested the hypothesis that combined inhibition of nNOS and iNOS will reduce neuronal damage and the inflammatory response induced by perinatal hypoxia-ischaemia (HI). In 12-day-old rats, HI was induced by right carotid artery occlusion followed by 90 min of 8% O2. Immediately upon reoxygenation, the rats were treated with NOS inhibitors (n = 24) or placebo (n = 24). Neuropathology was scored at 6 weeks after HI on a 4-point scale (n = 12 per group). The expression of heat shock pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…20 Eight-micron-thick coronal sections were stained with anti-GRK2, horseradish peroxidase-conjugated goat anti-rabbit antibody (Biotin), and Vectastain-ABC (Vector Laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…20 Eight-micron-thick coronal sections were stained with anti-GRK2, horseradish peroxidase-conjugated goat anti-rabbit antibody (Biotin), and Vectastain-ABC (Vector Laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, measurement of the areas of the left and right hemisphere indicated that 2-iminobiotin is only neuroprotective at a dose of 30 mg/kg per day. In previous studies, neuropathological scores, area measurements, or weight measurements of the ipsilateral and contralateral hemispheres were used to quantify the extent of neuroprotection in the Vannucci-Rice rat model (Bagenholm et al, 1996;Hagberg et al, 1997;Taylor et al, 2002;van den Tweel et al, 2002;Vannucci et al, 1998;Yuan et al, 2001). In the present study, two different methods of quantification of the cerebral injury resulted in slightly different results.…”
Section: Discussionmentioning
confidence: 74%
“…Next, we focused on the short-term effects of 2-iminobiotin after hypoxia-ischemia and reperfusion, using the optimal dose of 30 mg/kg per day. The presence of HSP70 in brain tissue has been suggested to be an early marker of injury (Ferriero et al, 1990;van den Tweel et al, 2002). Therefore, to investigate whether reduced HSP70 expression can be used as an early indicator of neuroprotection, we determined the effects of 2-iminobiotin administration on HSP70 expression at 24 hours after hypoxiaischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations